Review of Critical Thinking Ability as an Indicator in Solving Mathematical Problems Based on Representation - Hijriani, Lailin; Siahaan, Meiva Marthaulina Lestari; Simamarta, Justin Eduardo; Salsinha, Cecilia Novianti; Mone, Ferdinandus (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to describe student’s critical thinking ability in solving mathematical problems based on the type of representation used when solving the given problems. The study was conducted in 9th grade in junior high school in Kefamenanu, Timor Tengah Utara, NTT, Indonesia. Three respondents were selected from 28 students who were given a critical thinking ability test based on the completeness of their answers and then interviewed to clarify their answers. The instruments used in this study were test questions and interview guidelines. Test data obtained, has been analyzed based on Facione's critical thinking ability indicators which include interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results showed that student with symbolic representation, fulfilled 4 indicators of critical thinking ability, namely interpretation, analysis, evaluation, and inference. Which means that symbolic representation tends to support deeper critical thinking indicators than visual or verbal. Where student with visual representation fulfilled the critical thinking skills indicators, namely analysis and evaluation. Meanwhile, student with verbal representation fulfilled 1 indicator, namely interpretation.